The Relative Ability of Earnings and Cash Flows Data in Forecasting Future Cash Flows: Evidence in Malaysia - Abdinassir, Ali Abdi (2012)
Purpose – The purpose of this thesis is to examine whether the free cash flow is related to earnings, dividends, depreciations, and capital expenditures. All these components have strong relationship with free cash flows in forecasting future cash flows for Malaysian companies. The general objective of this research study and central question is to investigate free cash flows affected by earnings, dividends, depreciations, capexs, and return on equity, return on asset, net income, net sales, and size of the firms in forecasting future cash flows in Malaysia. Design/methodology/approach - Using a sample of 100 companies listed on the main board of Bursa Malaysia between 2005 until 2010.The researcher apply the ordinary least squares and fixed-effects approaches to estimate their regression models. To evaluate the forecasting performance of the regression models, both within-sample and out-of-sample forecasting tests are employed. Findings – This study provided evidence that detailed cash flow from operations has more power in predicting future cash flows than earnings and traditional cash flow measures. Based on sample of 100 Malaysian Companies between 2005-2010 shows that independent variables and depreciation has strong relationship to dependable variable which is Free Cash Flows. The predictability of both earnings DPS, Capexs, depreciations have highly statistically significant to cash flows. The main findings based the results shows EBITDA is the highest affected of free cash flows while DPS is lowest affected by free cash flows. Originality/value –The value of this study indicates that EBITDA received much attention in corporate finance because EBITDA involves fewer components than cash flows making it easier to forecast. EBITDA differs from the operating cash flow in a cash flow statement primarily by excluding payments for taxes or interest as well as changes in working capital. EBITDA also differs from free cash flow because it excludes cash requirements for replacing capital assets (capex)